Electoral Competition and Social Spending in the Argentine Provinces - Gonzalez, Lucas Isaac (2017)
What is the effect of political competition on subnational social spending? Using descriptive statistics and regression models for original budget panel data for the 24 Argentine provinces between 1993 and 2009, the study finds that social spending increases the more electorally secure governors are and the longer they have been in office. It also finds that other arguments in the literature are relevant in explaining variations on types of spending, such as partisan fragmentation in the districts. The article discusses these findings for the Argentine provinces and explores their implications with regard to the debates on the effects of electoral competition and the design of social policies, especially in developing countries and federal democracies.